Skills and roles of social worker within the social welfare institutions - Saddeek, Husein (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This study attempts to shed light on the important issue of social service issues, namely the professional skills and social roles that must be provided in a social worker. The establishment of a social worker His responsibilities and functions in a scientific contribute effectively to its success in a career , becoming specialist social, especially in our society , which is still the role of a social worker is absent or is activated as required . When owning a social worker package of professional skills and is able to do social his roles, it can help us to meet the customers’ needs and solving their problems within the social care institutions, This study could be a suitable reference to our colleagues specialists meetings in acquiring these skills and all their social roles that require him to their profession, and have a high degree of efficiency and achievement.